The Aucouturier Method in socio-affective development in 5-year-old children - Bada-Laura, Wendy N. (2023)
Social affective and psychomotor development in children guarantees their integral development, because the bases for subsequent learning are inscribed in them, hence our research problem: How does the Aucouturier method influence socio-affective development in five-year-old children? of Educational Institution No. 519 Pucalppa?, whose objective was to determine the influence of the Aucouturier method on socio-affective development in five-year-old children of Educational Institution No. 519 Pucallpa. The research was of a quantitative approach, applied type, explanatory level, experimental method and pre-experimental design. The intentional sample was made up of 22 5-year-old boys and girls, which was worked with a significance level of 5%. According to the pre-experimental design, the descriptive statistics (mean and standard deviation) and inferential statistics were used and to contrast the hypothesis, the Student's "t" test was used, in the application of the Aucouturier method, they have favored and improved significantly socio-affective development in 5-year-old children.